Protecting the Rights of Local Shareholders under the Saudi rules for Qualified Foreign Financial Institutions Investments in Listed Shares - Almutairi, Abdullah Mushkus (Journal of Economic, Administrative and Legal Sciences, 2020)
Recently, the Saudi Capital Market Authority (CMA) opened the door for foreign investors to invest directly in the stock exchange market (Tadawul) to gain more welfare from their investments. Along with this step, the CMA released a set of Rules for Qualified Foreign Financial Institutions Investments (RQFFII) in Listed Shares 2015 that aimed to attract and protect the shareholders’ rights. In this research project, the RQFFII have been examined to discover the level of attraction that these Saudi rules offer to foreign investment. The project also aimed to highlight strengths and weaknesses in the rules with regard to the protection shareholders’ rights. This thesis explored the possible influence of foreign investments in the Saudi stock exchange. The research project aimed to increase the CMA and shareholders’ awareness and knowledge in regard to these rules which lead to more protection of the local stock exchange. In order to achieve this goal, this thesis used a qualitative method by comparing these rules to the regulations of other countries that have a successful record, such as the Gulf Countries Council (GCC) and Australia. It has also analysed reports of the international organization to support the findings. The findings showed that on the one hand the current rules are not sufficiently attractive, and on the other hand are restricted and able to provide enough protection to the domestic market and shareholders. In addition, the results support the positive role of foreign investors on the local stock exchange market and its regulations. The findings implied a correlation between regulations and foreign investment flows in regard to attracting foreign investments and protecting the local economy. Hence, Saudi policymakers use the gradual opening of foreign investors to its stock exchange, this project found that the amended rules in 2016 may lead to more foreign investment inflow.